Radical candor : be a kick-ass boss without losing your humanity - Scott, Kim, (Kim Malone) (St. Martin's Press, 2019)
The idea is simple: You don't have to choose between being a pushover and a jerk. Using Radical Candor<U+2015>avoiding the perils of Obnoxious Aggression, Manipulative Insincerity, and Ruinous Empathy<U+2015>you can be kind and clear at the same time. Kim Scott was a highly successful leader at Google before decamping to Apple, where she developed and taught a management class. Since the original publication of Radical Candor in 2017, Scott has earned international fame with her vital approach to effective leadership and co-founded the Radical Candor executive education company, which helps companies put the book's philosophy into practice. Radical Candor is about caring personally and challenging directly, about soliciting criticism to improve your leadership and also providing guidance that helps others grow. It focuses on praise but doesn't shy away from criticism<U+2015>to help you love your work and the people you work with.